Phase separation of a binary mixture with an external force field. (14th December 2022) - Bertei, Antonio; Mauri, Roberto
Graphical abstract: Highlights: Phase separation of binary mixture with external force described by phase field model. External force leverages the thermodynamic repulsion of partially miscible species. In stable conditions the mixture experiences stratification. Phase separation from unstable region is fast and dictated by Bond number. In metastable conditions first the mixture stratifies and then nucleation proceeds. Abstract: Phase separation in liquid mixtures in presence of external forces is studied here using the phase field model. A thermodynamic analysis identifies the equilibrium distribution of species, showing that the external force leverages on the thermodynamic repulsion between partially miscible species by spreading stratification beyond what would happen in ideal conditions. The dynamic behavior of the mixture is described in terms of three characteristic numbers (i.e., fluidity, Schmidt and Bond numbers), where the Bond number dictates the timescale of mixture evolution. Three cases are considered, where the mixture is assumed to be initially in a stable, unstable or metastable state. In all cases, the external force breaks the symmetry of the process. When the mixture is initially unstable, phase separation is a fast spinodal decomposition, leading to a complete segregation of phases. For initially metastable mixtures, the external force primarily induces species stratification, followed by a much slower nucleation process.